On the change of Hodonyms of Sjenica from the onomastic and sociolinguistic aspect - Tubić Tamara (Glasnik Etnografskog Instituta SANU)
From the onomastic and sociolinguistic aspect, this work examines the way of changing of hodonyms of Sjenica, considering the decision which was made in this city in 2019. which said that each street should have its own name (unlike the previous situation which meant that several different sections of space, that could be called streets, had the same name).The result of that was the increase of hodonyms in Sjenica from 51 to 204. By using on the spot work and analytical statistical method (which included the examination of material obtained on the spot), it was obvious that there were 24 hodonyms left, and on the other hand, 180 of 204 new names were completely new hodonyms. Considering that Sjenica is a multinational environment, it was important to notice the role of Serbian on one and Bosnian-Muslim provenance on the other side. It is very important to say that when we think of the issue from the linguistic point of view, it was examined to what extent the hodonyms of toponymic and anthroponymic origin are represented. It was also examined into which sphere of history and life we can place street names of anthroponymic origin.